Six cyanoacrylate pentadithiophene copolymerized sulfur coordination metal complexes as well as preparation method and application thereof

By preparing cyanoacrylate-based pentadithiophene copolymer sulfur coordination metal complexes as dye sensitizers, the problems of insufficient photovoltaic performance and thermal stability in dye-sensitized solar cells were solved, achieving high photoelectric conversion efficiency and good electrochemical performance.

CN119591843APending Publication Date: 2025-03-11XIANGTAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311154675.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In existing dye-sensitized solar cells, there is still room for improvement in the photovoltaic performance and thermal stability of dye sensitizers, especially in the D-A'-π-A structure. Research on auxiliary electron acceptors has not been fully developed to improve the electron-withdrawing ability of the electron acceptor part and reduce the electron recombination rate.

Method used

Six cyanoacrylate-based pentanodithiophene copolymer sulfur coordination metal complexes were designed and prepared. The benzodithiophene derivative BDTT was used as an electron donor and the sulfur coordination metal complex formed by the coordination of cyanoacrylate-based pentanodithiophene with metal was used as an auxiliary acceptor A' to form D-A'-π-A type dye sensitizers, thereby improving electron transport efficiency and stability.

Benefits of technology

The photoelectric conversion efficiency of dye-sensitized solar cells was improved, with photoelectric conversion efficiencies of 5.81%, 7.03%, 8.21%, 9.42%, 10.08%, and 11.18%, respectively. Among them, the efficiency of BDTT-DCDA-Hg reached 11.18%, which has good electrochemical and thermal performance and is suitable for practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591843A_ABST
    Figure CN119591843A_ABST
Patent Text Reader

Abstract

The invention relates to six cyanoacrylate pentadithiophene copolymerized sulfur coordination metal complexes as shown in a formula 1, namely BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd and BDTT-DCDA-Hg, a preparation method of the six cyanoacrylate pentadithiophene copolymerized sulfur coordination metal complexes, and application of the six cyanoacrylate pentadithiophene copolymerized sulfur coordination metal complexes as a dye sensitizer in a dye-sensitized solar cell. According to the polymeric complex dye sensitizer, cyanoacrylate pentadithiophene is used as a main ligand, a sulfur coordination metal complex formed by metal coordination is used as an auxiliary electron acceptor A ', benzodithiophene bithiophene (BDTT) is used as an electron donor D, and a D-A'-pi-A type copolymerized complex is synthesized through Yamamoto coupling reaction. Experiments show good effects in photovoltaic performance tests of a dye-sensitized solar cell based on the copolymerized complex dye sensitizer: the photoelectric conversion efficiencies respectively reach 5.81%, 7.03%, 8.21%, 9.42%, 10.08% and 11.18%, the photoelectric conversion efficiencies (PCE) of BDTT-DCDA-Cd and BDTT-DCDA-Hg exceed 10%, the photoelectric conversion efficiency (PCE) of BDTT-DCDA-Hg reaches 11.18%, and the photoelectric conversion efficiency (PCE) of BDTT-DCDA-Hg exceeds 10%. The compound has high photoelectric conversion efficiency at present, the glass transition temperature and the thermal decomposition temperature of the compound are both 138 DEG C or above, and the thermal stability is good, so that the compound has certain prospects in development and application of dye-sensitized solar cells; # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to six cyanoacrylate-based pentanedithiophene copolysulfide coordination metal complexes and a preparation method and application thereof, and use thereof as dye sensitizers, which is the research and development and application of photoelectric sensitizing materials in dye-sensitized solar cells (DSSCs), and belongs to the field of photoelectric materials in new materials. Background Art

[0002] Compared with traditional silicon solar cells, dye-sensitized solar cells (DSSCs) are a type of solar photovoltaic conversion device with great application prospects, due to their low raw material cost and insensitivity to the angle of light received during operation. As an important component of DSSCs, dye sensitizers have been studied and developed by many scientists. In order to continuously improve the photovoltaic performance of dye sensitizers, they have evolved from their initial DA structure to the D-π-A structure, and then to the popular D-A'-π-A structure. For the D-A'-π-A structure, an auxiliary electron acceptor A' is introduced on the basis of the D-π-A structure to increase the electron-pulling ability of the electron acceptor part and reduce electron recombination, making the D-A'-π-A structure dye-sensitizer dye-sensitized solar cells (DSS Cs) has made a new breakthrough in the photoelectric conversion efficiency, and at the same time effectively improved other photoelectric properties of DSSCs, such as thermal stability. Therefore, the research on auxiliary electron acceptor A' has become a research hotspot in the field of DSSCs. The present invention studies the use of sulfur-coordinated metal complexes with strong electron-withdrawing ability and adjustable electron-withdrawing ability by adjusting the strength of the coordination bond as auxiliary electron acceptor A', and designs and prepares six cyanoacrylate-based pentanedithiophene copolymer sulfur-coordinated metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg. The test data show good photovoltaic performance. Summary of the invention

[0003] The purpose of the present invention is to provide and prepare six cyanoacrylate pentyldithiophene copolymer sulfur-coordinated metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg, which are used as D-A'-π-A type dye sensitizers in dye-sensitized solar cells. The polymer complexes use benzodithiophene derivative BDTT as electron donor D and sulfur-coordinated metal complexes formed by coordination of cyanoacrylate pentyldithiophene with metal as auxiliary The acceptor A' uses 2-cyano-3-(8-hydroxyquinoline-5-yl) acrylic acid as a π bridge and anchoring group, and polymerizes the electron donor D and the electron absorber part (-A'-π-A) through a Yamamoto coupling reaction to form the above six co-sulfur coordination metal complexes. The polymer complexes have good photoelectric conversion efficiency and thermal stability. The photoelectric conversion efficiency of the dye-sensitized solar cell based on the above six polymer complexes as dye sensitizers is 5.81%, 7.03%, 8.21%, 9.42%, 10.08%, and 11.18%, respectively. The general structural formula is as shown in Formula 1:

[0004] Preparation methods of six cyanoacrylate-based pentanedithiophene co-polysulfide-coordinated metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg:

[0005] (1) Preparation of ethyl 2-bromo-3-thiophenecarboxylate:

[0006] 2-bromo-3-thiophenecarboxylic acid and ethanol are added to a single-mouth round-bottom flask in a molar ratio of 1.0:1.2 to 1.0:1.8, and then concentrated sulfuric acid is added, and the mixture is heated to 75°C and refluxed for 16 to 20 hours. After the reaction is completed, the mixture is cooled to room temperature, and then added to water, and extracted with ethyl acetate for three times. The organic phase is collected and dried over anhydrous magnesium sulfate, filtered, and then spin-dried to obtain brown oily liquid 2-bromo-3-thiophenecarboxylic acid ethyl ester;

[0007] (2) Preparation of ethyl 2,2'-thiophene-3-carboxylate:

[0008]

[0009] Ethyl 2-bromo-3-thiophenecarboxylate and 2-thiopheneboric acid are added to a single-necked flask in a molar ratio of 1.0:1.1 to 1.0:1.5, and then tetrakis(triphenylphosphine), palladium, K2CO3, and a mixed solution of THF and H2O (volume ratio of 4:1 to 6:1) are added, and heated to 80°C under nitrogen protection and refluxed for 46 to 50 hours. After the reaction is completed, the mixture is allowed to stand for 10 to 14 hours, deionized water is added, and extracted three times with ethyl acetate. The organic phase is collected and dried with anhydrous magnesium sulfate, filtered and then spin-dried to obtain a light yellow liquid crude product, and the obtained crude product is separated by column using a mixed solution of dichloromethane and petroleum ether in a volume ratio of 1:28 to 1:32 as an eluent to obtain a yellow-green liquid product ethyl 2,2'-thiophene-3-carboxylate;

[0010] (3) Preparation of 2,2'-thiophene-3-carboxylic acid:

[0011] Add ethyl 2,2'-thiophene-3-carboxylate to a single-necked flask, then add anhydrous methanol and a NaOH aqueous solution, heat to 70°C and reflux for 0.4-0.6h. After the reaction is completed, cool to room temperature, pour into water and neutralize with dilute hydrochloric acid to a pH of 1.0, filter and wash the filtrate, and then dry it in a vacuum drying oven to obtain a light green solid product 2,2'-thiophene-3-carboxylic acid;

[0012] (4) Preparation of 4H-penta[2,1-b:3,4-b']dithiophene-4-one:

[0013] 2,2'-thiophene-3-carboxylic acid is added to a single-necked flask, and then thionyl chloride is added. The temperature is raised to 95°C, and then stirred and refluxed for 16 to 20 hours. After removing excess thionyl chloride, dichloromethane is added to dissolve, and then anhydrous aluminum chloride is added under nitrogen protection. The mixture is stirred for 0.8 to 1.2 hours in an ice bath, and then heated to room temperature and stirred for 22 to 26 hours. After the reaction is completed, deionized water is added and extracted three times with dichloromethane. The organic phase is collected and dried with anhydrous magnesium sulfate, filtered, and then spin-dried to near saturation and then cooled to obtain a crude product. The obtained crude product is separated by column using a mixed solution of ethyl acetate and petroleum ether with a volume ratio of 1:18 to 1:22 as an eluent to obtain a brown-red product 4H-penta[2,1-b:3,4-b']dithiophene-4-one;

[0014] (5) Preparation of 2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-one:

[0015] 4H-penta[2,1-b:3,4-b']dithiophene-4-one and N-bromosuccinimide were added to a round-bottom flask at a molar ratio of 1.0:2.7 to 1.0:2.9, and then DMF was added. The mixture was heated to 80°C and stirred and refluxed for 22 to 26 hours. After the reaction was completed, the mixture was cooled to room temperature and poured into ice water, and then filtered, and the filtered solid was dried to obtain a purple-red solid product 2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-one;

[0016] (6) Preparation of ethyl 2-cyano-2-(2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-ylidene)acetate:

[0017] 2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-one and ethyl 2-cyanoacetate are added to a round-bottom flask in a molar ratio of 1.0:1.1 to 1.0:1.3, and then benzene and piperidine are added. The temperature is raised to 80°C and then stirred and refluxed for 22 to 26 hours. After the reaction is completed, excess benzene is removed and extracted three times with ethyl acetate. The organic phase is collected and dried with anhydrous magnesium sulfate, and then spin-dried to near saturation to obtain a crude product. The obtained crude product is separated by column using a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 1:78 to 1:82 as an eluent to obtain a light purple solid ethyl 2-cyano-2-(2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-ylidene)acetate;

[0018] (7) The preparation process of 2-cyano-3-(8-hydroxyquinoline-5-yl) acrylic acid is shown in document (CN105294558A)

[0019] (8) Preparation of metal complex DCDA-Co:

[0020] Add ethyl 2-cyano-2-(2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-ylidene)acetate and 2-cyano-3-(8-hydroxyquinoline-5-yl)acrylic acid in a molar ratio of 1.0:0.8 to 1.0:1.2 into a two-necked bottle, then add THF, and then stir to dissolve at room temperature, then dissolve Co(OAc)24H2O in anhydrous methanol, and slowly dropwise add it through a constant pressure funnel, and react at 80°C for 22 to 26 hours. After the reaction is completed, cool to room temperature, put it in a refrigerator overnight, and then filter it, and then wash it with water three times and anhydrous ethanol three times, respectively, to finally obtain a dark green solid Co-containing complex DCDA-Co;

[0021] (9) Preparation of metal complex DCDA-Ni:

[0022] The synthesis method of the complex DCDA-Ni is the same as that of DCDA-Co, except that Co(OAc)24H2O is replaced by Ni(OAc)2·4H2O, and finally a black solid Ni-containing complex DCDA-Ni is obtained;

[0023] (10) Preparation of metal complex DCDA-Cu:

[0024] The synthesis method of the complex DCDA-Cu is the same as that of DCDA-Co, except that Co(OAc)24H2O is replaced with Cu(OAc)2, and finally a yellow solid Cu-containing complex DCDA-Cu is obtained;

[0025] (11) Preparation of metal complex DCDA-Zn:

[0026] The synthesis method of the complex DCDA-Zn is the same as that of DCDA-Co, except that Co(OAc)24H2O is replaced by Zn(OAc)22H2O, and finally a brown-green solid Zn-containing complex DCDA-Zn is obtained;

[0027] (12) Preparation of metal complex DCDA-Cd:

[0028] The synthesis method of the complex DCDA-Cd is the same as that of DCDA-Co, except that Co(OAc)24H2O is replaced with Cd(OAc)2·2H2O, and finally a brown-yellow solid Cd-containing complex DCDA-Cd is obtained;

[0029] (13) Preparation of metal complex DCDA-Hg:

[0030] The synthesis method of the complex DCDA-Hg is the same as that of DCDA-Co, except that Co(OAc)24H2O is replaced with Hg(OAc)2, and finally a brown solid Hg-containing complex DCDA-Hg is obtained;

[0031] (14) Preparation of polymer complex BDTT-DCDA-Co:

[0032] Add the Co-containing complex DCDA-Co and 2,6-dibromo-4,8-di(5-(2-ethyloctyl)thiophene-2-yl)benzo[1,2-b:4,5-b']dithiophene (BDTT) in a molar ratio of 1.0:0.8 to 1.0:1.2 into a three-necked flask, then add zinc powder, triphenylphosphine, delta-bis(triphenylphosphine)nickel dichloride and 2,2'-bipyridine in sequence, dissolve the mixture with DMF, heat to 90°C and reflux for 46 to 50 hours under nitrogen protection, filter after the reaction, wash three times with anhydrous ethanol, and dry to obtain a brown-black solid polymer complex BDTT-DCDA-Co;

[0033] (15) Preparation of polymer complex BDTT-DCDA-Ni:

[0034] The synthesis method of the polymer complex BDTT-DCDA-Ni is the same as that of BDTT-DCDA-Co, except that the Co-containing complex DCDA-Co is replaced with the metal complex DCDA-Ni, and finally a brown-green solid polymer complex BDTT-DCDA-Ni is obtained;

[0035] (16) Preparation of polymer complex BDTT-DCDA-Cu:

[0036] The synthesis method of the polymer complex BDTT-DCDA-Cu is the same as that of BDTT-DCDA-Co, except that the Co-containing complex DCDA-Co is replaced with the metal complex DCDA-Cu, and finally a yellow-green solid polymer complex BDTT-DCDA-Cu is obtained;

[0037] (17) Preparation of polymer complex BDTT-DCDA-Zn:

[0038] The synthesis method of the polymer complex BDTT-DCDA-Zn is the same as that of BDTT-DCDA-Co, except that the Co-containing complex DCDA-Co is replaced with the metal complex DCDA-Zn, and finally a yellow-green solid polymer complex BDTT-DCDA-Zn is obtained;

[0039] (18) Preparation of polymer complex BDTT-DCDA-Cd:

[0040] The synthesis method of the polymer complex BDTT-DCDA-Cd is the same as that of BDTT-DCDA-Co, except that the Co-containing complex DCDA-Co is replaced with the metal complex DCDA-Cd, and finally a brown-black solid polymer complex BDTT-DCDA-Cd is obtained;

[0041] (19) Preparation of polymer complex BDTT-DCDA-Hg:

[0042] The synthesis method of the polymer complex BDTT-DCDA-Hg is the same as that of BDTT-DCDA-Co, except that the Co-containing complex DCDA-Co is replaced with the metal complex DCDA-Hg, and finally a dark brown solid polymer complex BDTT-DCDA-Hg is obtained;

[0043] Uses of six cyanoacrylate-based pentanedithiophene co-polysulfide-coordinated metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg: Used as dye sensitizers for absorbing sunlight and generating and transmitting electrons in dye-sensitized solar cells;

[0044] The main advantages of this invention are: (1) six cyanoacrylate-based pentanedithiophene copolymer sulfur-coordinated metal complexes are invented. The polymer complexes use a benzodithiophene derivative (BDTT) with strong electron-donating ability as the donor D, a sulfur-coordinated metal complex formed by the coordination of cyanoacrylate-based pentanedithiophene with a metal as the auxiliary receptor A', 2-cyano-3-(8-hydroxyquinoline-5-yl) acrylic acid with a metal to form a π bridge, receptor A and an anchoring group, and the donor and the complex receptor part -A'-π-A are connected by a Yamamoto reaction to synthesize a polymer complex. The polymer complex has good The photoelectric conversion efficiency is 5.81%, 7.03%, 8.21%, 9.42%, 10.08% and 11.18% respectively. Among them, the photoelectric conversion efficiency (PCE) of BDTT-DCDA-Cd and BDTT-DCDA-Hg exceeds 10%, and the photoelectric conversion efficiency (PCE) of BDTT-DCDA-Hg reaches 11.18%, which is currently a very high photoelectric conversion efficiency; (2) The preparation method is simple and the raw materials are easily available; (3) It has good electrochemical properties, thermal properties and photostability. Its glass transition temperature and thermal decomposition temperature are both above 138°C, which is conducive to practical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The nuclear magnetic resonance hydrogen spectrum of the ligand 2-bromo-3-thiophenecarboxylic acid ethyl ester synthesized in the embodiment of the present invention is ( 1 H-NMR) (400MHz, CDCl3, ppm);

[0046] Figure 2 The nuclear magnetic resonance hydrogen spectrum of the ligand 2,2'-thiophene-3-carboxylic acid ethyl ester synthesized in the embodiment of the present invention ( 1 H-NMR) (400MHz, CDCl3, ppm);

[0047] Figure 3 The nuclear magnetic resonance hydrogen spectrum of the ligand 2,2'-thiophene-3-carboxylic acid synthesized in the embodiment of the present invention is ( 1 H-NMR) (400MHz, CDCl3, ppm);

[0048] Figure 4The nuclear magnetic resonance hydrogen spectrum of the ligand 4H-penta[2,1-b:3,4-b']dithiophene-4-one synthesized in the embodiment of the present invention is ( 1 H-NMR) (400MHz, CDCl3, ppm);

[0049] Figure 5 The nuclear magnetic resonance hydrogen spectrum of the ligand 2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-one synthesized in the embodiment of the present invention is ( 1 H-NMR) (400MHz, CDCl3, ppm);

[0050] Figure 6 The hydrogen nuclear magnetic resonance spectrum of the ligand 2-cyano-2-(2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-ylidene)acetic acid ethyl ester synthesized in the embodiment of the present invention is ( 1 H-NMR) (400MHz, CDCl3, ppm);

[0051] Figure 7 Infrared spectra (FT-IR) (KBr, cm -1 );

[0052] Figure 8 The infrared spectra (FT-IR) (KBr, cm) of the polymer complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg synthesized in the embodiments of the present invention are shown in Table 1. -1 );

[0053] Fig. 9 Thermogravimetric analysis curves (TGA) (N2, 20°C / min) of the polymer complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg synthesized in the embodiments of the present invention;

[0054] Fig.10 Current density-voltage (JV) curves of dye-sensitized solar cells using the polymer complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg synthesized in the embodiments of the present invention as dye sensitizers;

[0055] Fig.11 External quantum efficiency (IPCE) curves of dye-sensitized solar cells using the polymer complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg synthesized in the embodiments of the present invention as dye sensitizers. DETAILED DESCRIPTION

[0056] The reaction synthesis routes of the six cyanoacrylate-based pentanedithiophene co-polysulfide-coordinated metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg of the present invention are shown in Formula 2:

[0057]

[0058]

[0059] The present invention will be further described below in conjunction with specific embodiments.

[0060] Embodiment 1:

[0061] The molecular structures of the six cyanoacrylate-based pentanedithiophene co-polysulfide-coordinated metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg are shown in Formula 1;

[0062] Preparation of the above six cyanoacrylate-based pentanedithiophene co-polysulfide-coordinated metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg:

[0063] A. Preparation of ethyl 2-bromo-3-thiophenecarboxylate: 35 g 2-bromo-3-thiophenecarboxylic acid (0.1691 mol), 150 mL ethanol (2.5738 mol), and 5 mL concentrated sulfuric acid were added to a 250 mL single-mouth round-bottom flask, heated to 75 ° C, refluxed and stirred for 18 h, and after the reaction was completed, the mixture was poured into a 500 mL separatory funnel in three batches, 200 mL deionized water was poured each time, and extracted with EtOAc (3×50 mL), the organic phase was dried and filtered, and the filtrate was spin-dried to obtain 34.97 g of a brown-yellow oily liquid with a yield of 88%, FT-IR (KBr, cm -1):3100(C=CH),2960,2854(CH),1709(C=O),1625(C=C),1460,1378(CH),1058(C=S),506(C-Br), H NMR( 1 H-NMR) see attached Figure 1 , 1 H-NMR(CDCl3,ppm):7.35-7.36(d,1H),7.20-7.21(d,1H),4.31-4.36(q,2H),1.35-1.39(t,3H), 13 C-NMR(CDCl3,ppm):161.92,131.17,132.39,129.33,119.67,60.97,14.28;

[0064] B. Preparation of ethyl 2,2'-thiophene-3-carboxylate: 34.97 g of ethyl 2-bromo-3-thiophenecarboxylate (0.1488 mol), 22.85 g of 2-thiopheneboric acid (0.1786 mol), 1.72 g of tetrakis(triphenylphosphine), palladium (1.49 mmol), 61.69 g of K2CO3 (0.4464 mol) was added to a 500 mL round-bottom three-necked flask in turn, and then 300 mL of a mixture of THF and H2O (volume ratio of 5:1) was added, and the mixture was heated to 80°C and refluxed for 48 h under nitrogen protection. After the reaction was completed, the mixture was transferred to a separatory funnel in batches, 150 mL of deionized water was added each time, and extracted with EtOAc (3×50 mL). The organic phase was dried over anhydrous sodium sulfate, and then filtered and the filtrate was collected. The solvent was removed by a rotary evaporator to obtain a light yellow liquid crude product. The crude product was separated by silica gel column chromatography, and the eluent used was petroleum ether (EA) and dichloromethane (DCM) in a ratio of 30:1 (v / v), to obtain 18.44 g of a yellow-green liquid product with a yield of 52%, 150 mL of dichloromethane and 2.22 g 1,2-Dithiophene-1,2-dione (10 mmol) was added to a 250 mL single-necked flask and stirred for 5 min, then 8.1 g FeCl3 (50 mmol) was slowly added, and the mixture was reacted at 45 °C for 24 h. After the reaction was completed, the mixture was allowed to stand for 1 h, 300 ml of water was added, and the mixture was extracted three times with dichloromethane. The organic phase was collected and dried over anhydrous magnesium sulfate, filtered and dried to obtain a black flocculent solid. The crude product was separated by column using ethyl acetate and petroleum ether in a volume ratio of 1:12 as eluent to obtain 1.76 g of a black needle-shaped solid with a yield of 80%. FT-IR (KBr, cm -1 ):3108(=CH),2964,2852(CH),1709(C=O),1627(C=C),1460,1378(CH),1052(C=S), H NMR(1 H-NMR) see attached Figure 2 , 1 H-NMR(CDCl,ppm):7.48-7.49(d,1H),7.41-7.42(d,1H),7.36-7.37(d,1H), 7.18-7.19(d,1H),7.05-7.07(q,1H),4.32-4.37(q,2H),1.36-1.40(t,3H), 13 C-NMR (CDCl3, ppm): 163.14, 143.05, 133.86, 130.40, 129.20, 128.10, 127.60, 127.06, 123.92, 60.74, 14.21;

[0065] C. Preparation of 2,2'-thiophene-3-carboxylic acid: 18.44 g of ethyl 2,2'-thiophene-3-carboxylate (77.37 mmol) was added to a 250 mL single-necked flask, followed by anhydrous methanol (100 ml) and NaOH aqueous solution (10 mL; 2 M), and the mixture was heated to 70°C and refluxed for 12 h. After the reaction, the mixture was cooled to room temperature, and then poured into a 400 mL beaker and adjusted to pH 1 with 10% dilute hydrochloric acid. The filtrate was filtered and washed, and then dried in a vacuum drying oven to obtain 14.97 g of a light green solid product with a yield of 92%; mp 143.5-144.3°C, FT-IR (KBr, cm -1 ):3437(OH),3102(=CH),1700(C=O),1625(C=C),1053(C=S), H NMR( 1 H-NMR) see attached Figure 3 , 1 H-NMR (DMSO-d6, ppm): 7.64-7.65 (d, 1H), 7.53-7.54 (d, 1H), 7.44-7.45 (d, 1H), 7.38-7.39 (d, 1H), 7.09-7.11 (q, 1H). 1 H-NMR spectrum is not shown here. 13 C-NMR spectrum assisted in proving that 13 C-NMR (DMSO-d6, ppm): 164.40, 141.93, 133.88, 130.96, 129.52, 128.98, 128.87, 127.94, 125.70. Among them, the chemical shift of the carbon atom in the carboxyl group is 164.40;

[0066] D. Preparation of 4H-penta[2,1-b:3,4-b']dithiophene-4-one: 14.97 g 2,2'-thiophene-3-carboxylic acid (71.18 mmol) was added to a 100 mL three-necked flask, and then 40 mL thionyl chloride was added. The mixture was heated to 95°C and stirred under reflux for 18 h. After removing the excess thionyl chloride, 60 mL dichloromethane was added to dissolve it. Then, 28.47 g anhydrous aluminum chloride (0.2136 mol) was added under nitrogen protection. The mixture was stirred in an ice bath for 1 h, and then heated to room temperature and stirred for 24 h. After the reaction was completed, the mixed solution was Pour into a 500 mL separatory funnel and add deionized water (250 mL), then extract with DCM (3×50 mL), dry the organic phase with anhydrous magnesium sulfate and filter, evaporate the filtrate to near saturation and then cool, separate the crude product by silica gel column chromatography, the eluent is EA and EtOAc in a volume ratio of 20:1, and obtain 3.83 g of brown-red product with a yield of 28%, mp 177.8-178.5°C; FT-IR (KBr, cm -1 ):3096(C=CH),1701(C=O),1460,1378(CH),1046(C=S),1H-NMR see attached Figure 4 , 1 H-NMR(CDCl3,ppm):7.01-7.03(d,2H),6.97-6.98(d,2H), 13 C-NMR(CDCl3,ppm):182.78,149.25,142.45,127.18,121.76;

[0067] E. Preparation of 2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-one: 3.83 g 4H-penta[2,1-b:3,4-b']dithiophene-4-one (19.93 mmol), 9.93 g N-bromosuccinimide (55.81 mmol) and 50 mL DMF were added in sequence into a 100 mL round-bottom flask. The mixture was refluxed in an oil bath at 80°C for 24 h. After cooling to room temperature, the mixture was poured into ice water and then filtered. The filtered solid was dried to obtain 6.00 g of a purple-red solid with a yield of 86%. The mp was 195.3-195.9°C. FT-IR (KBr, cm -1 ):3100(=CH),1701(C=O),1654(C=C),1052(C=S),507(C-Br), nuclear magnetic resonance hydrogen spectrum (1H-NMR) see attached Figure 5 , 1 H-NMR(CDCl3,ppm):7.00(s,2H), 13C-NMR(CDCl3,ppm):180.52,148.69,139.55,124.44,113.95;

[0068] F. Preparation of ethyl 2-cyano-2-(2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-ylidene)acetate: 3 g of 2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-one (8.57 mmol), 1.16 g of Ethyl 2-cyanoacetate (10.29 mmol) was added to a dried 50 ml single-mouth round-bottom flask, and then 30 ml of benzene was measured and added to dissolve it, and then 30 drops of piperidine were added as a catalyst. The mixture was refluxed in an 80 ° C oil bath for 24 h. After the reaction was completed, excess benzene was removed, and then extracted with ethyl acetate (3×30 mL). After the organic layer was dried, the solvent was removed to obtain a crude product. The crude product was separated by column separation. The eluent used was EA and EtOAc in a volume ratio of 80:1, and 2.14 g of light purple solid was obtained. The yield was 56%, mp226.1-226.7 ° C, FT-IR (KBr, cm -1 ):3431(-OH),3102(C=CH),2958,2854(CH),2213(C≡N),1730(C=O),1572(C=N),1050(C=S),648(C-Br), H NMR( 1 H-NMR) see attached Figure 6 , 1 H-NMR(CDCl3,ppm):7.78(s,1H),7.67(s,1H),4.37-4.42(q,2H),1.39-1.43(t,3H), 13 C-NMR (CDCl3, ppm):161.11,148.19,145.20,143.72,140.90,138.99,130.67,127.06,115.67,113.13,111.98,100.74,63.11,14.09;

[0069] G. Preparation of Co-containing complex DCDA-Co: 0.3566 g of ethyl 2-cyano-2-(2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-ylidene)acetate (0.8087 mmol), 0.1940 g 2-Cyano-3-(8-hydroxyquinolin-5-yl)acrylic acid (0.8087mmol) was added to a 50mL two-necked bottle, 20mL THF was measured and added thereto, and the mixture was stirred at room temperature for 30min to dissolve it, and then 0.2055g (0.8249mmol) Co(OAc)24H2O was dissolved in anhydrous methanol (10mL) and added dropwise through a constant pressure funnel, and the addition was completed in about 30min. The temperature was raised to 80°C and refluxed in an oil bath for 24h. After the reaction was completed, it was cooled and placed in an ice bath overnight. Most of the solid was precipitated, filtered, and washed three times with deionized water and anhydrous ethanol respectively, to obtain 0.4001g of dark green solid, with a yield of 62%. The temperature was raised to 40°C to dissolve it, and then 0.149g HgCl2 (0.55mmol) was dissolved in 20mL of anhydrous methanol and slowly added dropwise through a constant pressure funnel. The temperature was raised to 75℃ and the reaction was carried out for 24h. After the reaction was completed, the mixture was cooled to room temperature and placed in a refrigerator overnight to allow the solid to completely precipitate. After filtration, the mixture was washed with water three times and with anhydrous ethanol three times respectively to obtain a light yellow solid (0.256g) with a yield of 59.6%. The infrared spectrum (FT-IR) is attached. Figure 7 , FT-IR (KBr, cm -1 ):3437(-OH),2925,2854(CCH),2212(C≡N),1705(C=O),1582(C=C),1513(C=N),1112(CO-Co),1056(C=S),538(O-Co),511(N-Co),474(S-Co);

[0070] H. Preparation of Ni-containing complex DCDA-Ni: This reaction is the same as the synthesis method of DCDA-Co, except that 0.2055g Co(OAc)24H2O (0.8249mmol) is replaced with 0.2052g Ni(OAc)24H2O (0.8249mmol). Finally, 0.3892g of black solid is obtained with a yield of 60%. The infrared spectrum (FT-IR) is attached. Figure 7 , FT-IR (KBr, cm -1 ):3437(-OH),2925,2854(CCH),2212(C≡N),1705(C=O),1582(C=C),1514(C=N),1113(CO-Co),1056(C=S),538(O-Ni),512(N-Ni),475(S-Ni);

[0071] I. Preparation of Cu-containing complex DCDA-Cu: This reaction is the same as the synthesis method of DCDA-Co, except that 0.2055 g Co(OAc)24H2O (0.8249 mmol) is replaced with 0.1647 g Cu(OAc)2 (0.8249 mmol). Finally, 0.3861 g of yellow solid is obtained with a yield of 58%. The infrared spectrum (FT-IR) is attached. Figure 7 , FT-IR (KBr, cm -1 ):3437(-OH),2925,2854(CCH),2212(C≡N),1705(C=O),1580(C=C),1512(C=N),1111(CO-Co),1054(C=S),536(O-Cu),509(N-Cu),472(S-Cu);

[0072] J. Preparation of Zn-containing complex DCDA-Zn: This reaction is the same as the synthesis method of DCDA-Co, except that 0.2055g Co(OAc)24H2O (0.8249mmol) is replaced with 0.1821g Zn(OAc)22H2O (0.8249mmol). Finally, 0.4069g of brown-green solid is obtained with a yield of 61%. The infrared spectrum (FT-IR) is attached. Figure 7 , FT-IR (KBr, cm -1 ):3437(-OH),3113(C=CH),2925,2854(CCH),2212(C≡N),1705(C=O),1578(C= C),1511(C=N),1108(CO-Co),1052(C=S),533(O-Zn),506(N-Zn),469(S-Zn);

[0073] K. Preparation of Cd-containing complex DCDA-Cd: This reaction is the same as the synthesis method of DCDA-Co, except that 0.2055g Co(OAc)24H2O (0.8249mmol) is replaced with 0.2210g Cd(OAc)22H2O (0.8249mmol). Finally, 0.3904g of brown solid is obtained with a yield of 55%. The infrared spectrum (FT-IR) is attached. Figure 7 , FT-IR (KBr, cm -1 ):3437(-OH),3113(C=CH),2925,2854(CCH),2212(C≡N),1705(C=O),1574(C= C),1509(C=N),1106(CO-Co),1047(C=S),529(O-Cd),502(N-Cd),463(S-Cd);

[0074] L. Preparation of Hg-containing complex DCDA-Hg: This reaction is the same as the synthesis method of DCDA-Co. Only 0.2055g Co(OAc)24H2O (0.8249mmol) is replaced with 0.2643g Hg(OAc)2 (0.8249mmol). Finally, 0.4594g of brown solid is obtained with a yield of 59%. The infrared spectrum (FT-IR) is attached. Figure 7 , FT-IR (KBr, cm -1 ):3437(-OH),3113(C=CH),2925,2854(CCH),2212(C≡N),1705(C=O),1570(C= C),1507(C=N),1104(CO-Co),1042(C=S),524(O-Hg),497(N-Hg),458(S-Hg);

[0075] M. Preparation of polymer complex BDTT-DCDA-Co: Under N2 protection, 0.3342g (0.4537mmol) donor monomer (BDTT), 0.3640g (0.4537mmol) cobalt complex monomer (DCDA-Co), 0.2968g (0.4537mmol) dichlorobis(triphenylphosphine)nickel, 0.2380g (0.9074mmol) triphenylphosphine, 0.1483g (2.2685mmol) activated zinc powder and 0.0071g (0.0454mmol) 2,2'-bipyridine were added to a 50ml three-necked flask in sequence. The mixture was dissolved with 20mL DMF, heated to 90°C and refluxed for 48h. After the reaction was completed, it was completely cooled, filtered, and the filter residue was washed three times with anhydrous ethanol. After complete drying, 0.1257g of brown-black solid was obtained with a yield of 52%. The infrared spectrum (FT-IR) is attached. Figure 8 , FT-IR (KBr, cm -1 ):3437(-OH),2925,2854(CCH),2212(C≡N),1662(C=O),1582(C=C),1513(C= N),1112(CO-Co),1056(C=S),538(O-Co),511(N-Co),474(S-Co),Mn=8.75×10 3 g / mol, PDI = 2.24;

[0076] N. Preparation of polymer complex BDTT-DCDA-Ni: The synthesis method of this polymer is the same as that of BDTT-DCDA-Co. It only requires replacing 0.3640g of cobalt complex monomer DCDA-Co (0.4537mmol) with 0.3639g of nickel complex monomer DCDA-Ni (0.4537mmol). Finally, 0.1148g of brown-green solid was obtained with a yield of 50%. The infrared spectrum (FT-IR) is attached. Figure 8 , FT-IR (KBr, cm -1 ):3437(-OH),2925,2854(CCH),2212(C≡N),1705(C=O),1582(C=C),1513(C= N),1112(CO-Co),1056(C=S),538(O-Co),511(N-Co),474(S-Co),Mn=7.83×10 3 g / mol, PDI = 2.20;

[0077] O. Preparation of polymer complex BDTT-DCDA-Cu: The synthesis method of this polymer is the same as that of BDTT-DCDA-Co. It is only necessary to replace 0.3640g of cobalt complex monomer DCDA-Co (0.4537mmol) with 0.3661g of copper complex monomer DCDA-Cu (0.4537mmol). Finally, 0.1269g of yellow-green solid was obtained with a yield of 51%. The infrared spectrum (FT-IR) is attached. Figure 8 , FT-IR (KBr, cm -1 ):3437(-OH),2925,2854(CCH),2212(C≡N),1705(C=O),1582(C=C),1513(C= N),1112(CO-Co),1056(C=S),538(O-Co),511(N-Co),474(S-Co),Mn=7.99×10 3 g / mol, PDI = 2.17;

[0078] P. Preparation of polymer complex BDTT-DCDA-Zn: The synthesis method of this polymer is the same as that of BDTT-DCDA-Co. It is only necessary to replace 0.3640g of cobalt complex monomer DCDA-Co (0.4537mmol) with 0.3670g of zinc complex monomer DCDA-Zn (0.4537mmol). Finally, 0.1285g of yellow-green solid was obtained with a yield of 53%. The infrared spectrum (FT-IR) is attached. Figure 8 , FT-IR (KBr, cm -1):3437(-OH),2925,2854(CCH),2212(C≡N),1705(C=O),1582(C=C),1513(C= N),1112(CO-Co),1056(C=S),538(O-Co),511(N-Co),474(S-Co),Mn=9.17×10 3 g / mol, PDI = 2.13;

[0079] Q. Preparation of polymer complex BDTT-DCDA-Cd: The synthesis method of this polymer is the same as that of BDTT-DCDA-Co. It is only necessary to replace 0.3640g of cobalt complex monomer DCDA-Co (0.4537mmol) with 0.3883g of cadmium complex monomer DCDA-Cd (0.4537mmol). Finally, 0.1304g of brown-black solid was obtained with a yield of 48%. The infrared spectrum (FT-IR) is attached. Figure 8 , FT-IR (KBr, cm -1 ):3437(-OH),2925,2854(CCH),2212(C≡N),1705(C=O),1582(C=C),1513(C= N),1112(CO-Co),1056(C=S),538(O-Co),511(N-Co),474(S-Co),Mn=9.08×10 3 g / mol, PDI = 2.09;

[0080] R. Preparation of polymer complex BDTT-DCDA-Hg: The synthesis method of this polymer is the same as that of BDTT-DCDA-Co. Only 0.3640g of cobalt complex monomer DCDA-Co (0.4537mmol) is needed to be replaced with 0.4283g of mercury complex monomer DCDA-Hg (0.4537mmol). Finally, 0.1385g of dark brown solid is obtained with a yield of 45%. The infrared spectrum (FT-IR) is attached. Figure 8 , FT-IR (KBr, cm -1 ):3437(-OH),2925,2854(CCH),2212(C≡N),1705(C=O),1582(C=C),1513(C= N),1112(CO-Co),1056(C=S),538(O-Co),511(N-Co),474(S-Co),Mn=8.94×10 3 g / mol,PDI=2.15.

[0081] Embodiment 2:

[0082] Thermogravimetric analysis (TGA) curves of six cyanoacrylate-based pentanedithiophene co-polysulfide coordination metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg were measured. Method: The test was performed using a SDTQ600 thermogravimetric analyzer under N2 protection at a heating rate of 20°C / min. The thermogravimetric analysis (TGA) curves are shown in Figure 2. Fig. 9 , the test results are shown in Table 1:

[0083] Table 1 Molecular weight test results and thermal performance data of six cyanoacrylate-based pentanedithiophene copolymers with sulfur-coordinated metal complexes

[0084]

[0085] Embodiment 3:

[0086] The molecular weights of six cyanoacrylate-based pentanedithiophene co-polysulfide-coordinated metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg were determined by gel permeation chromatography (GPC): a Waters-1515 gel permeation chromatograph was used, and the separation columns were waters styragel columns (103, 104, ), the column oven temperature was 80°C, DMF was used as the mobile phase, polystyrene solution was used as the reference, and the flow rate was 1.00 mL / min. The test results are shown in Table 1.

[0087] Embodiment 4:

[0088] Photovoltaic performance test of six cyanoacrylate-based pentanedithiophene co-polysulfide coordination metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg: Current density-current (JV) curve test light source is a xenon lamp simulating a light intensity of 100 mW / cm 2 AM 1.5G sunlight was used to change the voltage and record the change of current with voltage through Keithley 2400 digital source meter; the external quantum efficiency (IPCE) test was performed by Oriel Cornerstone

[0089] Table 2 Photovoltaic performance test results of six cyanoacrylate-based pentanedithiophene copolymers with sulfur-coordinated metal complexes

[0090]

[0091] The colorimeter provides the light source and the measurement is performed under short-circuit conditions. The wavelength test interval is 10nm and the effective working area of ​​DSSCs is 0.25cm 2 The performance parameters and photoelectric conversion efficiency of dye-sensitized solar cells using six polymer complex dye sensitizers BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg were determined. The battery current density-voltage (JV) curves are shown in Figure 2. Fig.10 , the battery external quantum efficiency (IPCE) curve is as follows Fig.11 ; Table 2 is their photovoltaic performance and photoelectric conversion efficiency test results. The results show that the photoelectric conversion efficiency (PCE) of BDTT-DCDA-Cd and BDTT-DCDA-Hg exceeds 10%, and the photoelectric conversion efficiency (PCE) of BDTT-DCDA-Hg reaches 11.18%, which is currently a very high photoelectric conversion efficiency.

Claims

1. Six cyanoacrylate-based pentanedithiophene co-polysulfide-coordinated metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg, whose structural formulas are as follows: The preparation methods of the above six cyanoacrylate-based pentanedithiophene copolymerized sulfur-coordinated metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg are as follows: (1) Preparation of ethyl 2-bromo-3-thiophenecarboxylate: 2-bromo-3-thiophenecarboxylic acid and ethanol are added to a single-mouth round-bottom flask in a molar ratio of 1.0:1.2 to 1.0:1.8, and then concentrated sulfuric acid is added, and the mixture is heated to 75°C and refluxed for 16 to 20 hours. After the reaction is completed, the mixture is cooled to room temperature, and then added to water, and extracted with ethyl acetate for three times. The organic phase is collected and dried over anhydrous magnesium sulfate, filtered, and then spin-dried to obtain brown oily liquid 2-bromo-3-thiophenecarboxylic acid ethyl ester; (2) Preparation of ethyl 2,2'-thiophene-3-carboxylate: Ethyl 2-bromo-3-thiophenecarboxylate and 2-thiopheneboric acid are added to a single-necked flask in a molar ratio of 1.0:1.1 to 1.0:1.5, and then tetrakis(triphenylphosphine), palladium, K2CO3, and a mixed solution of THF and H2O (volume ratio of 4:1 to 6:1) are added, and heated to 80°C under nitrogen protection and refluxed for 46 to 50 hours. After the reaction is completed, the mixture is allowed to stand for 10 to 14 hours, deionized water is added, and extracted three times with ethyl acetate. The organic phase is collected and dried with anhydrous magnesium sulfate, filtered and then spin-dried to obtain a light yellow liquid crude product, and the obtained crude product is separated by column using a mixed solution of dichloromethane and petroleum ether in a volume ratio of 1:28 to 1:32 as an eluent to obtain a yellow-green liquid product ethyl 2,2'-thiophene-3-carboxylate; (3) Preparation of 2,2'-thiophene-3-carboxylic acid: Ethyl 2,2'-thiophene-3-carboxylate was added to a single-necked flask, and then anhydrous methanol and NaOH aqueous solution were added. The temperature was raised to 70°C and refluxed for 0.4-0.6h. After the reaction was completed, the mixture was cooled to room temperature, poured into water and neutralized with dilute hydrochloric acid to a pH of 1.

0. The filtrate was filtered and washed, and then dried in a vacuum drying oven to obtain a light green solid product 2,2'-thiophene-3-carboxylic acid. (4) Preparation of 4H-penta[2,1-b:3,4-b']dithiophene-4-one: 2,2'-thiophene-3-carboxylic acid is added to a single-necked flask, and then thionyl chloride is added. The temperature is raised to 95°C, and then stirred and refluxed for 16 to 20 hours. After removing excess thionyl chloride, dichloromethane is added to dissolve, and then anhydrous aluminum chloride is added under nitrogen protection. The mixture is stirred for 0.8 to 1.2 hours in an ice bath, and then heated to room temperature and stirred for 22 to 26 hours. After the reaction is completed, deionized water is added and extracted three times with dichloromethane. The organic phase is collected and dried with anhydrous magnesium sulfate, filtered, and then spin-dried to near saturation and then cooled to obtain a crude product. The obtained crude product is separated by column using a mixed solution of ethyl acetate and petroleum ether with a volume ratio of 1:18 to 1:22 as an eluent to obtain a brown-red product 4H-penta[2,1-b:3,4-b']dithiophene-4-one; (5) Preparation of 2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-one: 4H-penta[2,1-b:3,4-b']dithiophene-4-one and N-bromosuccinimide were added to a round-bottom flask at a molar ratio of 1.0:2.7 to 1.0:2.9, and then DMF was added. The mixture was heated to 80°C and stirred and refluxed for 22 to 26 hours. After the reaction was completed, the mixture was cooled to room temperature and poured into ice water, and then filtered, and the filtered solid was dried to obtain a purple-red solid product 2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-one; (6) Preparation of ethyl 2-cyano-2-(2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-ylidene)acetate: 2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-one and ethyl 2-cyanoacetate are added to a round-bottom flask in a molar ratio of 1.0:1.1 to 1.0:1.3, and then benzene and piperidine are added. The temperature is raised to 80°C and then stirred and refluxed for 22 to 26 hours. After the reaction is completed, excess benzene is removed and extracted three times with ethyl acetate. The organic phase is collected and dried with anhydrous magnesium sulfate, and then spin-dried to near saturation to obtain a crude product. The obtained crude product is separated by column using a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 1:78 to 1:82 as an eluent to obtain a light purple solid ethyl 2-cyano-2-(2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-ylidene)acetate; (7) The synthesis process of 2-cyano-3-(8-hydroxyquinoline-5-yl) acrylic acid is shown in document (CN105294558A) (8) Preparation of metal complex DCDA-Co: Add ethyl 2-cyano-2-(2,6-dibromo-4H-penta[2,1-b:3,4-b']dithiophene-4-ylidene)acetate and 2-cyano-3-(8-hydroxyquinoline-5-yl)acrylic acid in a molar ratio of 1.0:0.8 to 1.0:1.2 into a two-necked bottle, then add THF, and then stir to dissolve at room temperature, then dissolve Co(OAc)24H2O in anhydrous methanol, and slowly dropwise add it through a constant pressure funnel, and react at 80°C for 22 to 26 hours. After the reaction is completed, cool to room temperature, put it in a refrigerator overnight, and then filter it, and then wash it with water three times and anhydrous ethanol three times, respectively, to finally obtain a dark green solid Co-containing complex DCDA-Co; (9) Preparation of metal complex DCDA-Ni: The synthesis method of the complex DCDA-Ni is the same as that of DCDA-Co, except that Co(OAc)24H2O is replaced by Ni(OAc)2·4H2O, and finally a black solid Ni-containing complex DCDA-Ni is obtained; (10) Preparation of metal complex DCDA-Cu: The synthesis method of the complex DCDA-Cu is the same as that of DCDA-Co, except that Co(OAc)24H2O is replaced with Cu(OAc)2, and finally a yellow solid Cu-containing complex DCDA-Cu is obtained; (11) Preparation of metal complex DCDA-Zn: The synthesis method of the complex DCDA-Zn is the same as that of DCDA-Co, except that Co(OAc)24H2O is replaced by Zn(OAc)22H2O, and finally a brown-green solid Zn-containing complex DCDA-Zn is obtained; (12) Preparation of metal complex DCDA-Cd: The synthesis method of the complex DCDA-Cd is the same as that of DCDA-Co, except that Co(OAc)24H2O is replaced with Cd(OAc)2·2H2O, and finally a brown-yellow solid Cd-containing complex DCDA-Cd is obtained; (13) Preparation of metal complex DCDA-Hg: The synthesis method of the complex DCDA-Hg is the same as that of DCDA-Co, except that Co(OAc)24H2O is replaced with Hg(OAc)2, and finally a brown solid Hg-containing complex DCDA-Hg is obtained; (14) Preparation of polymer complex BDTT-DCDA-Co: Add the Co-containing complex DCDA-Co and 2,6-dibromo-4,8-di(5-(2-ethyloctyl)thiophene-2-yl)benzo[1,2-b:4,5-b']dithiophene (BDTT) in a molar ratio of 1.0:0.8 to 1.0:1.2 into a three-necked flask, then add zinc powder, triphenylphosphine, delta-bis(triphenylphosphine)nickel dichloride and 2,2'-bipyridine in sequence, dissolve the mixture with DMF, heat to 90°C and reflux for 46 to 50 hours under nitrogen protection, filter after the reaction, wash three times with anhydrous ethanol, and dry to obtain a brown-black solid polymer complex BDTT-DCDA-Co; (15) Preparation of polymer complex BDTT-DCDA-Ni: The synthesis method of the polymer complex BDTT-DCDA-Ni is the same as that of BDTT-DCDA-Co, except that the Co-containing complex DCDA-Co is replaced with the metal complex DCDA-Ni, and finally a brown-green solid polymer complex BDTT-DCDA-Ni is obtained; (16) Preparation of polymer complex BDTT-DCDA-Cu: The synthesis method of the polymer complex BDTT-DCDA-Cu is the same as that of BDTT-DCDA-Co, except that the Co-containing complex DCDA-Co is replaced with the metal complex DCDA-Cu, and finally a yellow-green solid polymer complex BDTT-DCDA-Cu is obtained; (17) Preparation of polymer complex BDTT-DCDA-Zn: The synthesis method of the polymer complex BDTT-DCDA-Zn is the same as that of BDTT-DCDA-Co, except that the Co-containing complex DCDA-Co is replaced with the metal complex DCDA-Zn, and finally a yellow-green solid polymer complex BDTT-DCDA-Zn is obtained; (18) Preparation of polymer complex BDTT-DCDA-Cd: The synthesis method of the polymer complex BDTT-DCDA-Cd is the same as that of BDTT-DCDA-Co, except that the Co-containing complex DCDA-Co is replaced with the metal complex DCDA-Cd, and finally a brown-black solid polymer complex BDTT-DCDA-Cd is obtained; (19) Preparation of polymer complex BDTT-DCDA-Hg: The synthesis method of the polymer complex BDTT-DCDA-Hg is the same as that of BDTT-DCDA-Co, except that the Co-containing complex DCDA-Co is replaced with the metal complex DCDA-Hg, and finally a dark brown solid polymer complex BDTT-DCDA-Hg is obtained.

2. The use of the six cyanoacrylate-based pentanedithiophene co-polysulfide-coordinated metal complexes BDTT-DCDA-Co, BDTT-DCDA-Ni, BDTT-DCDA-Cu, BDTT-DCDA-Zn, BDTT-DCDA-Cd, and BDTT-DCDA-Hg according to claim 1 as dye sensitizers in dye-sensitized solar cells.

Citation Information

Patent Citations

  • 2-cyano-3-(8-hydroxyquinoline-5-yl)acrylic acid, and preparation method and applications thereof

    CN105294558A